Approximate and Exact Solution of Linear and Nonlinear Schrödinger Equation using Sawi Transform coupled with Homotopy Perturbation Method - Olubanwo, Oludapo O.; Adepoju, Julius; Ajani, Abiodun Sufiat; Idowu, Senayon Sunday; Ifeyemi, Opeyemi (Universitas Brawijaya, 2024)
This study presents an approximate solution using the Sawi Transform Method for the Schrödinger equation. Four problems were considered to illustrate the Sawi Transform Homotopy perturbation Method’s (STHPM) effectiveness and capabilities. The equation below is subjected to the Sawi Transform combined with Homotopy Perturbation Method (STHPM). it psi(z,t)+Δ[ψ(z,t)]+Nψ(z,t)=0 The results obtained are represented in a series of rapidly convergent terms.